Studi Kandungan Fitokimia Ekstrak Etanol Daun Gambir Asal Aceh Tenggara Sebagai Anti Diabetes - Vera Viena; Muhammad Nizar (Fakultas Teknik, 2018)
Indonesia is one of tropical countries that rich in natural resources. It has more than a thousand of medicinal plants. This study focused on assessing the potential of phytochemical content gambir leaves from Southeast Aceh as an alternative of antidiabetes through inhibition of alpha amylase enzyme. Steps of research to be conducted consist of: (1) Making dry simplisia from gambir leaves; extraction of gambir leaves by maceration for 2x24 hours and screening done every 24 hours, and solvent evaporation to obtain the dry extract of gambir; (2) Analysis of phytochemical (phenolic, flavonoid and tannin) content of ethanol extract of gambir leaves; and (3) Analysis of chemical components using GC-MS. The results showed that the moisture content of powder gambir leaves was 3,017%, which is still below the national standard. The ethanol extract contained a rendement of 2,47 gr / gr of dry weight. The inhibition activity of alpha amylase enzyme was obtained at a sample concentration of 1000 ppm , e.i 88.22%. The more active a sample in inhibiting the action of the alpha-amylase enzyme, the less the 3-amino-5-nitrosalisilic acid formed in the second stage of enzyme activation. The results of phytochemicalanalysis of ethanol extract of gambir leaves from Southeast Aceh showed secondary metabolite content such as Total Phenolic, Total Flavonoid, and Tanin respectively of 71, 80; 32, 06 and 58.39%. The chemical components, e.i the total phenolics, flavonoids and tannins have been reported to have antidiabetic activity by lowering blood sugar levels after inhibition testing via the alpha amylase enzyme.